Evaluasi Kelayakan Finansial Pasar Bareng Kota Malang Hasil Revitalisasi Sebagai Pasar Multifungsi - Nasikh Nasikh; Andhika Widianto Rahardjo (Masyarakat Ekonomi Syariah Bogor, 2022)
In realizing the economic growth of a region, many aspects need to be considered. One of the two aspects in realizing positive economic growth of a region is infrastructure and trade. The development of an infrastructure or project needs to cost money, moreover the project is not a small project. Therefore, there needs to be an in-depth and structured study and research before the project is funded or has been funded so as to know the prospects of the project. The study and research used an analysis of the financial feasibility study for the development of Pasar Bareng in Malang City with the aim of seeing the financial feasibility of developing Pasar Bareng. A project feasibility study has the meaning of a study that can see if the project if it gets an investment can run well and provide financial benefits. This study uses the Net Present Value (NPV), Internal Rate of Return (IRR), and Benefit Cost Ratio (BCR) methods. The data that has been collected will be analyzed and get a project development perspective from a financial perspective. In this study there is a comparison of profit or loss obtained by looking at data from operational costs, income, and investment costs. The costs used come from maintenance and operational costs incurred during the operation of Pasar Bareng. The results of the feasibility analysis test using the Net Present Value method get a value of Rp. – 7,000,291,269,823. Then, the Benefit Cost Ratio method gets a value of Rp. 0,000,039,423,147. And the last method is the Internal Rate of Return method which gets a value of -1,373,149.77. From the results of this analysis, it can be concluded that the development of Pasar Bareng Malang City is not feasible to do. Key words: Feasibility Study, Pasar Bareng, Malang City.